Wide-spectrum modulated electrochromic smart windows based on MnO₂/PB films - Ma, Dongyun (2022)
Inorganic materials have been extensively studied for visible electrochromism in the past few decades. However, the single inorganic electrochromic (EC) material commonly exhibits a single color change, leading to a narrow spectrum of modulation, which offsets or limits the maximally energy-saving ability. Here, we present a wide-spectrum modulated EC device designed by combining the complementary EC nanocomposite of manganese dioxide (MnO2) and Prussian blue (PB) for enhanced energy savings. Porous MnO2 nanostructures serve as host frameworks for the templated growth of PB, resulting in MnO2/PB nanocomposites. The complementary optical modulation ranges of MnO2 and PB enable a widen-spectrum modulation across the solar region with the development of the MnO2/PB nanocomposite. The colored MnO2/PB device exhibited an optical modulation of 32.1% in the wide solar spectrum range of 320-1100 nm and blocked 72.0% of the solar irradiance. Furthermore, fast switching responses (2.7 s for coloration and 2.1 s for bleaching) and a high coloration efficiency (83.1 cm2·C-1) of the MnO2/PB EC device are also achieved. The high EC performance of the MnO2/PB nanocomposite device provides a new strategy for the design of high-performance energy-saving EC smart windows.